1972
DOI: 10.1302/0301-620x.54b3.499
|View full text |Cite
|
Sign up to set email alerts
|

Radial Tunnel Syndrome

Abstract: 1. Resistant cases of tennis elbow are explained on the basis of an entrapment neuropathy of the radial nerve and its branches. 2. An operation is described to explore these nerves through an anterior muscle-splitting incision. 3. Thirty-eight elbows in thirty-six patients have been operated on with improvement in all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
5

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(50 citation statements)
references
References 0 publications
1
30
0
5
Order By: Relevance
“…Nirschl has stated that the abnormality is in the origin of the extensor carpi radialis brevis and that the failure of others to demonstrate it can be attributed to its anatomical position underneath the extensor carpi radialis longus, which has to be retracted for proper visualization (Nirschl & Pettrone 1979, Nirschl 1977. Other authors are less certain, and almost every structure on the lateral side of the elbow has been implicated (Bosworth 1965, Newman & Goodfellow 1975, Roles & Maudsley 1972, Boyd & Macleod 1973. There is more agreement about the theory that tennis elbow is caused by overuse: this is supported by our finding that the dominant hand was involved in 84%, a figure which coincides with that of previous reports (Nirschl & Pettrone 1979, O'Neil et al 1980.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nirschl has stated that the abnormality is in the origin of the extensor carpi radialis brevis and that the failure of others to demonstrate it can be attributed to its anatomical position underneath the extensor carpi radialis longus, which has to be retracted for proper visualization (Nirschl & Pettrone 1979, Nirschl 1977. Other authors are less certain, and almost every structure on the lateral side of the elbow has been implicated (Bosworth 1965, Newman & Goodfellow 1975, Roles & Maudsley 1972, Boyd & Macleod 1973. There is more agreement about the theory that tennis elbow is caused by overuse: this is supported by our finding that the dominant hand was involved in 84%, a figure which coincides with that of previous reports (Nirschl & Pettrone 1979, O'Neil et al 1980.…”
Section: Discussionsupporting
confidence: 90%
“…Newman & Goodfellow (1975) noted chondromalacia of the radial head in some patients. Roles & Maudsley (1972) proposed that the symptoms might be caused by a radial nerve entrapment. Van Rossum et al (1978) produced evidence to oppose that view, and Heyse-Moore (1984) suggested that decompression of the radial nerve might also be releasing tension on the common extensor origin.…”
Section: Introductionmentioning
confidence: 99%
“…According to Roles and Maudsley score, 10 12 were excellent (52.17%), 6 good (26.08%), 3 acceptable (13.04%), and 2 cases were poor (8.69%).…”
Section: Resultsmentioning
confidence: 99%
“…10 Patients were reviewed at 6, 12, and 24 weeks post-treatment and at 3 months interval until the end of the study. …”
Section: Resultsmentioning
confidence: 99%
“…With radial nerve palsy due to SOL at the elbow, there are cases of PIN palsy as well as palsy of the superficial radial nerve. In addition, disorders featuring intense pain because of entrapment of the PIN have also been reported to differentiate it from lateral humeral epicondylitis l) 2) . We studied the clinical features and images along with surgical findings in cases of radial nerve palsy due to SOL of the elbow.…”
Section: Introductionmentioning
confidence: 99%